(untitled) - Kamilova, R.T.; Nosirova, A.R. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Sanitary-hygienic assessment of the conditions of education in educational institutions, the determination of their compliance with established sanitary and hygienic standards. Materials and methods: The studies were conducted in general education schools located in Mirzo Ulugbek, Yunusabad, Shayhantakhur districts of Tashkent city. Results: In primary schools of the Mirzo-Ulugbek district, the actual number of students exceeded the estimated number by the project by 9.8%, and in schools of Shaykhantakhur and Yunusabad districts - by 10%, water supply system malfunction (internal, external), defective sanitary equipment, non-fulfillment rules of student seating, insufficient natural lighting of the premises is confirmed by KEO values, which were in the range of 0.7 to 1% at a hygienic rate of 1.5%. Conclusions: In all surveyed of primary schools, the actual number of students exceeded the estimated number by an average of 10%; insufficient equipment was observed for sports equipment, water supply disruptions, the provision of non-rational student furniture, and violation of indoor light conditions